Eksperimen Material untuk Mebel dari Limbah Kertas Koran - Amelia, Tracy; Kusumarini, Yusita; Basuki, Lucky (Intra, 2018)
Newspapers production produce tons of waste every day throughout Indonesia. Although the waste generated will be recycled for the next newspapers production, the fiber contained in the paper has its limitation. The problem statement of this research is how to process the newspapers’ waste into material for the furniture manufacturing and its application to the test making of chair furniture and bench. For that, mixed methods will be used in the research, which is a method that combines the qualitative approach and quantitative approach in order to understand the research better. To support the quantitative method in this study, the newspapers sheets experiment was conducted into a newspapers panel. The material used is newspapers sheet glued per sheet.                Optimized newspaper panels are made using yellow glue solution and glue diluent with a 2:1 ratio. Each size of ¼ pages of newspaper requires 2.5 ml of yellow glue solution per sheet, so for the size of 1 page of newspaper requires as much as 10 ml per sheet. The resulting panel has unstable thickness and weight because the workmanship uses manpower. The thickness and size of the panel produced affects the strength of the newspapers panel, as well as material panels in general. In addition, the treatment for panel construction as a furniture material cannot be equated with the construction treatment of processed wood waste material although initially the newspaper is considered processed wood.